Mechanics of vitrimer particle compression and fusion under heat press. (1st July 2021) - Yu, Luxia; Sun, Xiaohao; Jin, Yinghua; Zhang, Wei; Long, Rong
Highlights: Finite element model of vitrimer particle compression under heat press accounts for random initial particle packing and non-uniform particle size. A cohesive zone model capturing the interface healing between vitrimer particles is implemented to simulate particle fusion. Simulation results reveal underlying mechanisms for the effects of particle size and processing conditions on vitrimer particle compression and fusion. Abstract: The compression and fusion of vitrimer particles is a fundamental problem underlying the recycling of vitrimers. Incomplete particle compression can lead to voids in the fused vitrimer, thereby impacting its mechanical property. In this work, we present a two-dimensional finite element model to capture the interplay of multiple complex mechanisms including random particle packing, large deformation, inter-particle contact, thermally activated bulk stress relaxation, and interface healing. Specifically, we focus on understanding two key components of this problem: i) evolution of porosity during compression and fusion of randomly packed vitrimer particles, and ii) effective tensile modulus and strength of fused vitrimer. Using the finite element model, we first show that using smaller particles can reduce the porosity in the fused vitrimer, which only slightly increases the effective modulus, but the increase in tensile strength is more pronounced. In addition, under the same processing conditions, particles with mixed sizes can achieve better densification and higher tensile strength after fusion than uniformly sized particles with the same average radius. Regarding the effects of processing conditions, we discuss how the porosity and effective modulus of the fused vitrimer depend on the processing time, temperature and pressure, and find a general trend consistent with experimental observations, i.e. longer processing time, higher temperature or higher pressure can lead to lower porosity and higher modulus of the fused vitrimer. The theoretical insights towards the compression and fusion process as well as the simulation framework can be useful in optimizing the powder-based heat press process of vitrimer and its composites. Graphical abstract: Image, graphical abstract